Performance of the Sofia SARS-CoV-2 Rapid Antigen Test in Symptomatic and Asymptomatic Pediatric Patients. Issue 9 (24th May 2022) - Freeman, Megan Culler; Freeman, Tanner J; Iagnemma, Jennifer; Rasmussen, Jayne; Heidenreich, Kelly; Wells, Alan; Hoberman, Alejandro; Mitchell, Stephanie L
Abstract: The sensitivity and specificity of SARS-CoV-2 antigen tests have not been widely assessed in children. We evaluated children presenting to outpatient care with Quidel Sofia SARS-CoV-2 antigen test (Sofia-Ag-RDT) compared against Cepheid Xpert Xpress SARS-CoV-2/Flu/RSV reverse transcriptase-polymerase chain reaction test from November 2020 to April 2021. Sofia-Ag-RDT had the highest sensitivity in symptomatic (82%; 95% confidence interval, 68%-91%) children. Abstract : Quidel Sofia SARS-CoV-2 antigen test has better diagnostic performance for SARS-CoV-2 infection in symptomatic children than in asymptomatic children.